Exendin-4 Protects MIN6 Cells from t-BHP-Induced Apoptosis via IRE1-JNK-Caspase-3 Signaling - Wen-Jia Chen; Lin-Xi Wang; Yan-Ping Wang; Zhou Chen; Xiao-Ying Liu; Xiao-Hong Liu; Li-Bin Liu (International Journal of Endocrinology, 2012)
Objectives. This study aimed to explore the effect of exendin-4 on t-BHP-induced apoptosis in pancreatic β cells and the mechanism of action. Methods. Murine MIN6 pancreatic β cells were treated with exendin-4 in the presence or absence of tert-butyl hydroperoxide (t-BHP). Cell survival was assessed by MTT staining. The percentage of apoptotic cells was determined by fluorescence microscopy analysis after Hoechst/PI staining and flow cytometric assay after Annexin V-FITC/PI staining. The activity of caspase-3 was determined using a caspase-3 activity kit. Expression of P-IRE1α, IRE1α, C-Jun N-terminal kinase (JNK), P-JNK, C-JUN, and P-C-JUN was detected by western blotting. Results. Exendin-4 was found to inhibit t-BHP-induced apoptosis in pancreatic β-cells by downregulating caspase-3 activity. Exendin-4 also inhibited the endoplasmic reticulum transmembrane protein IRE1, the apoptosis-related signaling molecule JNK, and c-Jun activation. Conclusions. Our findings suggest that exendin-4 ultimately reduces t-BHP-induced β-cell apoptosis. IRE1-JNK-c-Jun signaling is involved in the exendin-4-mediated modulation of β-cell apoptosis.